The Level of Digital Literacy and Its Impact for Self-Regulated and Effective Language Learning - Fuad Hasyim (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2021)
This study aims to discuss the effect of digital literacy level on independent language learning skills and effective learning abilities. The research respondents (n = 147) were the students of Universitas Islam Indonesia from various years who took English courses as General Education (MKU). Respondents were chosen randomly from students who participated in researcher English courses. This research is quantitative. The data was obtained through a Likert scale questionnaire with a range number; 0-1 and 1-5. The quantitative data were analyzed by correlation (Pearson product-moment) and regression (ANOVA) techniques. The results displayed; first, there is no significant effect of digital literacy variables on Self-Regulated language learning skills. Second, there is a substantial impact of digital literacy on effective learning abilities. Third, there is a significant impact of Self-Regulated language learning on effective language learning. This study suggested that higher education institutions need to provide formal programs in training or workshops to increase digital literacy capacity and student academic skills to achieve effective learning goals.